Orientasi masa depan dan minat melanjutkan studi Strata Dua (S2) - Amin, Amin; Niken Titi Pratitis; Isrida Yul Arifiana (INNER: Journal of Psychological Research, 2022)
This study aims to determine the relationship between future orientation and interest in continuing master's studies in students who are taking thesis courses at the Faculty of Psychology, University of 17 August 1945, Surabaya. This research is a type of quantitative research using correlational research. The research subjects were 98 which were divided into 2 gender groups, namely: 65 women and 33 men who were selected quota sampling technique. The data collection method was carried out through the distribution of online questionnaires using google form using a future orientation scale to measure future orientation and an interest scale in continuing master's studies to measure interest in continuing master's studies. The data analysis technique used in this study is the Sperman Rho correlation technique with the help of the SPSS (Statistical Product and Service Solution) version 25.0 for windows program. The results show that there is a very significant positive relationship between future orientation and interest in continuing master's studies, so this research hypothesis is accepted. This shows that the higher the future orientation of students, the higher their interest in continuing their master's studies. Likewise, if the future orientation of students is low, the interest in continuing their master's studies will be low. Keywords: Future orientation, Interest in continuing master's studies, Thesis student